Factors affecting motor development of toddlers who received cardiac corrective procedures during infancy. (July 2021) - Chien, Chia-Hui; Lee, Tzu-Ying; Lin, Ming-Tai
Abstract: Background: A risk adjustment in congenital heart surgery (RACHS-1) method was used for assessing quality of care in children undergoing congenital heart surgery. Children in RACHS-1 categories 1–4 had high survival rates. Little was known about these children and their prognosis of motor development during toddlerhood. Aims: To compare the differences between congenital heart disease (CHD) and healthy toddlers in terms of their characteristics, parental characteristics, parenting attitudes, and motor development, and further examine the influence of these factors on the motor development of the toddler with CHD. Study design: A comparison study. Subjects: There were 48 toddlers in the CHD group and 39 in the healthy toddler group. Outcomes measures: Current height and weight, Peabody Developmental Motor Scales second edition (PDMS-2), state-trait anxiety inventory (STAI) and Child Vulnerability Scale (CVS). Results: Compared to the healthy group, toddlers with CHD had lower birth weight, smaller height-for-age, lower weight-for-age, and more motor developmental delay, but their mothers had lower anxiety. A shorter length of hospitalization and higher weight-for-age z score predicted a better gross motor development, with 40.2% of the variance explained. A higher weight-for-age z score and low RACHS-1 categories predicted better total motor development, with 38.4% of the variance explained. Only low RACHS-1 categories predicted better fine-motor development, with 12% of the variance explained. Conclusions: Many children in RACHS-1 categories 1–4 had growth and motor development below average in their toddlerhood. Therefore, growth and developmental progress should be assessed and mediated early after corrective procedures. Highlights: RACHS-1 1–4 infants are at high risk of motor development delay after CHD surgery. Length of hospitalization and weight-for-age predicts infant motor function. Strategies for parents to facilitate infant growth and development are necessary.